Cerebrolysin improves peripheral inflammatory pain: Sex differences in two models of acute and chronic mechanical hypersensitivity. Issue 4 (25th March 2019) - Morales‐Medina, Julio C.; Flores, Gonzalo; Vallelunga, Annamaria; Griffiths, Natalie H.; Iannitti, Tommaso
Abstract: Chronic inflammatory pain is a major health problem worldwide with high prevalence in women. Cerebrolysin is a multimodal neuropeptide preparation that crosses the blood brain barrier and displays neuroprotective properties in aging and disease. Previously, we showed that cerebrolysin reduced mechanical allodynia in a model of persistent inflammation and pain. We aim to build upon the findings of our previous study by investigating the response to acute administration of cerebrolysin in two models of peripheral inflammation and assessing sex differences. We utilized the complete Freund's adjuvant (CFA) that produces maximal oedema and mechanical allodynia within days and carrageenan that produces similar effects within hours. Cerebrolysin reversed the mechanical allodynia in both sexes in CFA‐treated rats. On the other hand, in rats treated with carrageenan, cerebrolysin was only effective in reducing mechanical allodynia in female rats. In conclusion, the present study shows that cerebrolysin effects may be sex‐specific depending on different mechanisms that are at play in these two models of peripheral inflammatory pain. Further investigations are required to determine the factors contributing to sex differences.